2015
DOI: 10.1142/s1363919615400149
|View full text |Cite
|
Sign up to set email alerts
|

Crisis-Driven Innovation: The Case of Humanitarian Innovation

Abstract: Innovation is often presented as a survival issue and this provides a powerful metaphor to focus attention on the need to manage it effectively. But in the humanitarian context it takes on a very literal meaning. Crises, whether natural or man-made, require rapid problem solving if agencies and aid workers are to avoid the huge negative impacts of such disasters. That makes consideration of how innovation takes place in this sector an urgent challenge. How can the humanitarian sector best organise to enable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…In the current COVID‐19 pandemic, this approach implies an understanding of the biology of the peculiarities, root causes, and effects of the virus. Otherwise, strategies to cope with the pandemic become arbitrary, ad hoc, and rely on gut feelings (Müller, 1985; Cooper and Edgett, 2010; Bessant et al, 2015). In the case of the COVID‐19 virus, the human body reacts in the following manner: Cytokines are the proteins released as immune response against infections, genetic disorder, or autoimmune diseases (Testar, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current COVID‐19 pandemic, this approach implies an understanding of the biology of the peculiarities, root causes, and effects of the virus. Otherwise, strategies to cope with the pandemic become arbitrary, ad hoc, and rely on gut feelings (Müller, 1985; Cooper and Edgett, 2010; Bessant et al, 2015). In the case of the COVID‐19 virus, the human body reacts in the following manner: Cytokines are the proteins released as immune response against infections, genetic disorder, or autoimmune diseases (Testar, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Corporate decision makers have to react quickly, consider future effects, and simultaneously generate options to overcome the crisis here and now (Teece et al, 2016). These reactions are typically ad hoc and based on gut feelings instead of sufficient information (e.g., Müller, 1985; Cooper and Edgett, 2010; Bessant et al, 2015). For example, firms often cut their innovation investments despite negative long‐term consequences, as visible in reduced patent filings, forfeiting the firms’ future (Archibugi et al, 2013b; Hingley and Park, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis showed that the main limitations in the use of these approaches are: industry-specific limitations; the need to adapt to different economic realities; orientation to some single factor in the creation of high-tech products and their market promotion, difficulties in obtaining source data, etc. (Bessant et al, 2015). These restrictions significantly complicate the comprehensive assessment of the possibility of implementing projects to create high-tech products within a given time, especially in risk, in relation to Russian enterprises as well (Batkovskiy et al, 2015).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…A particular issue in this research field is the evolution of innovation in the presence of problems originating from harmful and unexpected events beyond more conventional (albeit potentially turbulent/disruptive) economic/market dynamics – i.e., crises – which have to be solved in a limited amount of time to minimize possible losses for a worst‐case scenario. Despite the urgency and unexpectedness of the crisis, it is very unlikely that its generated problems will be solved by an ad hoc action, hence, requiring systematic planning and coordination, that is, crisis management (Pearson and Clair, 1998; James et al, 2011), where innovation is a vital element (Laperche et al, 2011; Bessant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%